2021
DOI: 10.1007/s11356-021-15834-x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of dithiophenolato chitosan nanocomposites against carbon tetrachloride-induced hepatotoxicity in rats

Abstract: Our previous study showed that dithiophenolate (DTP) and its chitosan nanoparticles (DTP-CSNPs) have abilities to bind with DNA helixes. So in this study, their lethal doses (LD 50 ) and therapeutic roles against rat liver injuries induced by carbon tetrachloride (CCl 4 ) were evaluated. The study focused on the determination of the markers of oxidative stress (OS) and apoptosis and compare the results with those of cisplatin treatment. The results revealed that LD50 values of DTP and DTP-CSNPs are 2187.5 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…The destructive action of CCL4 is accredited to bio-alteration of cytochrome P4502E1 (CYP2E1) that produces vastly reactive trichloromethyl (CCL3•) free radicals which reacts with oxygen and gives trichloromethyl peroxyl (CCL3OO•) radicals that can attack the lipids and protein of cell membrane bounded to various organs (Zhao et al, 2022). The current study revealed that CCL4 disrupted the lipid metabolism by increasing TC, TG, LDL-c and vLDL-c and lowering HDL-c and these findings matched with previous work of (Shaban et al, 2022). Hypercholesteremia after CCL4 administration may be attributed to hindering the βoxidation of fatty acids (Mahmoodzadeh et al, 2017) and activation the esterification process of lipid (Mesalam et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…The destructive action of CCL4 is accredited to bio-alteration of cytochrome P4502E1 (CYP2E1) that produces vastly reactive trichloromethyl (CCL3•) free radicals which reacts with oxygen and gives trichloromethyl peroxyl (CCL3OO•) radicals that can attack the lipids and protein of cell membrane bounded to various organs (Zhao et al, 2022). The current study revealed that CCL4 disrupted the lipid metabolism by increasing TC, TG, LDL-c and vLDL-c and lowering HDL-c and these findings matched with previous work of (Shaban et al, 2022). Hypercholesteremia after CCL4 administration may be attributed to hindering the βoxidation of fatty acids (Mahmoodzadeh et al, 2017) and activation the esterification process of lipid (Mesalam et al, 2021).…”
Section: Discussionsupporting
confidence: 86%
“… GSH (glutathione), GSSG (reduced glutathione), GPx (glutathione peroxidase), SOD (superoxide dismutase), GST (glutathione-S-transferase), GSR (glutathione reductase), MDA (malonedialdehyde), TNF-α (tumor necrosis factor-α), and PDGF-BB (platelet-derived growth factor-BB), and TGF-β1 (transforming growth factor-beta1 and the data are being presented as the mean ± SD * CI values determine the type of impact between E and M. the effect can be evaluated as synergism (CI < 1), anti-synergism (CI > 1), or additive (CI = 1) (Zhou et al 2007 ; Habashy et al 2018 ; Shaban et al 2020 , 2021a , 2022 ) …”
Section: Resultsmentioning
confidence: 99%
“…* CI values determine the type of impact between E and M. the effect can be evaluated as synergism (CI < 1), anti-synergism (CI > 1), or additive (CI = 1) (Zhou et al 2007 ; Habashy et al 2018 ; Shaban et al 2020 , 2021a , 2022 )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations